A Review - Fire Fighting Robot based on Arduino - Hemalatha,; M. Rajesh,; K. Shenpriya,; N.K. Santhiya, (Journal of Power Electronics and Devices, 2022)
The firefighting robot is the subject of the review that is being given. Robots are capable of carrying out jobs more effectively, cheaply, and accurately than people. Because technology has advanced and made the human job easier, its popularity has increased. Affected zones are where the firefighting robot is programmed to look for and put out flames. The robot can move along the prescribed path without getting stuck in the barriers and moves while performing a fire scan. Through the use of the microcontroller module, it executes activities such as obstacle detection, flame detection, actuation, notifying, and extinguishing by evaluating the data under the supervision of the software. Mechanical system design and production, electronic system design and production, necessary software production. Draft drawings, measurements, computer-aided design software, and solid modeling tools were used during the design and development of the mechanical system. The study's robot was capable of locating fire sources that were put randomly near obstacles and extinguishing them using predetermined fire extinguishing systems. This particular sort of robot features a water ejector that can spray water when a fire first starts. Using a servo motor, the water ejector pipe can be moved in the desired direction. An Arduino UNO microcontroller manages the entire process.